ANALISIS IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 3 TAHUN 2013 TENTANG KAWASAN TANPA ROKOK DI PUSKESMAS INDUK KOTA SEMARANG - Azizah Nur Fatih; Kusyogo Cahyo; Aditya Kusumawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Public Health Services (Puskesmas) is one of the health care which obligatory needed at least one in every district. In total of 37 Public Health Services in Semarang Municipality, only 26 Public Health Services already been rated for its Tobacco Free Areas implementation (research by KPKTR and FKM Unimus)Ṫhe aim of this research is to analyze the implementation of Local Government Regulation Number 3 Year 2013 regarding Tobacco Free Areas in Public Health Services of Semarang Municipality. This research used quantitative method with cross-sectional approach, whereas 111 respondents were the samples gathered with total sampling method. The data were analyzed using univariate, bivariate and multivariate analysis. Univariate analysis showed in numbers that the good communication 66,7%, adequate resources 53,2%, agreeing disposition 53,2% and appropriate bureaucratic structure 79,3%. The result from crosstab shows that good implementation due to good communication 56.8 %, good implementation with adequate resources 64.4 %, good implementation with stakeholders’ approval 62.7 % and good implementation with appropriate bureaucracy structure by 58.0 %. Chi Square test (α=0,05) was used in bivariate analysis, showed the correspondent variables were resources (ρ value 0,011), disposition (ρ value 0,031), and bureaucratic structure (ρ value 0,034). Meanwhile there is no correlation with communication (ρ value 0,253). Multivariate analysis showed that resources, disposition, and bureaucratic structure is the dominant factors of the implementation of Local Government Regulation Number 3 Year 2013 regarding Tobacco Free Areas in Public Health Services of Semarang Municipality with R2 value 20,1%.